Análise das estratégias de leitura de alunos do ensino superior e seu reflexo na compreensão do texto - Lima, Maria de Fátima de Oliveira (2010)
The dissertation thesis is inserted in the line of Language Research, Education and Socio-Cultural Organization, with the theme: "Analysis of Reading Strategies of Students for Higher Education and its reflection in the Understanding of Text." This study has investigated the reading strategies used by students in courses of Letras and Pedagogia in Universidade Federal do Piauí, trying to understand the reading process of these students, from the use of questionnaires and interviews with tasks that were answered in order to detect until point the use of "conscious strategies" might favor a correct reading, critical and autonomous. This is a descriptive study which we seek in on the grounds of textual Linguistics, based on social interactionist approach, the understanding of the formation of competence for reading and, in the discursive approach, especially the testimony of academics, research participants on reading a text of opinion: For Mônica, wife of João, Luca's mother Ruth de Aquino of the magazine "Time", which served as a model for assessment of competence; well with the written text productions, which make up the corpus of this study. The analysis of qualitative and quantitative, enabled us to observe some factors that proved significant enough to highlight the importance of having a strategic mindset, understanding of texts through the application of strategies, ie, what we want to emphasize is the fact that the activity of reading, developed allows the use metacognitive, and thus aware of reading strategies. The study confirmed, through the model of Goodman's reading, the use of "conscious strategy" to calculate the meaning and use of prior knowledge on the extraction of inferences. Thus to suggest that teaching of metacognitive strategy can contribute to the formation of this type of mentality-the strategic-and suggesting proposals to the challenges faced by educators and learners, particularly with regard to the effectiveness of the academic reader. The procedures were handled in accordance with the propositions of Bardin (2002), Dr.Gaskell ; Bauer(2002), Ghiglione (1982) and based on studies of orality to the transcript oral text to written that texts of academics. Organized into Units and textual sense meaning.